SUCROSE LOSS IN THE HARVEST-LOADING-TRANSPORT SYSTEM AT SINDANG LAUT AND TERSANA BARU SUGAR MILLS, CIREBON - Tajuddin Bantacut, Sukardi dan Irfan Ardiansyah Supatma TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACT The loss of sucrose in the cane sugar production could reach 35 percents. Harvesting, loading and transporting the sugarcane contribute significantly to the total lost prior to milling, ranging from 5-25 percent. The aims of this research were to identify factors that influence the harvest-loading-transport system, to analyze the pattern of sucrose content loss in sugar cane before milling, and to recommend means of improving the harvest-loading-transport system according to the existing condition of sugar factories. The implementation of the harvest-loading-transport system could be influenced by many factors; among them were the factors that determine the harvesting schedule (T-score) which consist of planting time, difference between lowest and highest purity levels, average sucrose content, difference between upper and lower sucrose contents, maturity factor, increasing coefficient, durability coefficient, shoot borer, plant condition, and distance. The loading and transport system was determined by the plantation layout, infrastructure (road, bridge conditions), topography, climate and weather, and equipment for fire tackling. Keywords: sucrose losses, harvest-loading-transport, T-score